2017
DOI: 10.1002/rcm.7804
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐specific metabolite profiling of benzylisoquinoline alkaloids in the root of Macleaya cordata by combining laser microdissection with ultra‐high‐performance liquid chromatography/tandem mass spectrometry

Abstract: The integrated method is sensitive, specific and reliable for determining trace alkaloids, which is also a powerful tool for metabolite profiling of tissue-specific BIAs in situ. The present findings should contribute to a better understanding of the biosynthesis of BIAs in M. cordata root and provide scientific evidence for its quality evaluation based on morphological characteristics. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 53 publications
4
17
0
Order By: Relevance
“…In general, it is difficult to identify the unknown constituents from mass spectra without information about the fragment ions and retention times. The fragmentation mechanism of Macleaya alkaloids can be summarized based on the findings of previous studies . Target profiling and identification of BIAs in the extracted samples from the fresh aerial parts of M. microcarpa were exclusively based on retention time (<0.25 min), exact mass (M + , [M + H] + , and [M + Na] + ions, mass error<10 ppm), and MS/MS product ions in a database of the accurate mass of known compounds and the mass spectral fragmentation behavior of Macleaya alkaloids.…”
Section: Resultsmentioning
confidence: 99%
“…In general, it is difficult to identify the unknown constituents from mass spectra without information about the fragment ions and retention times. The fragmentation mechanism of Macleaya alkaloids can be summarized based on the findings of previous studies . Target profiling and identification of BIAs in the extracted samples from the fresh aerial parts of M. microcarpa were exclusively based on retention time (<0.25 min), exact mass (M + , [M + H] + , and [M + Na] + ions, mass error<10 ppm), and MS/MS product ions in a database of the accurate mass of known compounds and the mass spectral fragmentation behavior of Macleaya alkaloids.…”
Section: Resultsmentioning
confidence: 99%
“…In some previous studies, the fragmentation behaviours or characteristic fragment ions of benzyltetrahydroisoquinoline [12][13][14][15] , aporphine 10,[14][15][16] , tetrahydroprotoberberine 8,10,[12][13][14][15]17 , protopine 10,14,15 , protoberberine 8,10,11,14,15,[17][18][19] , N-methyltetrahydroprotoberberine 14,15 , dihydrobenzo-phenanthridine 14,15 , benzophenanthridine 14,15,20,21 , chelidonine 22 , morphine 23 , narciclasine 24 , phthalideisoquinoline 25 , ipecac 26 , and bisbenzyltetrahydroxyisoquinoline 27 have been investigated. However, comparative studies on the fragmentation pathways of these isoquinoline alkaloids have rarely been reported, which leads to the neglect of some interesting and characteristic fragmentation patterns.…”
mentioning
confidence: 99%
“…Compounds 17–22 were speculated to be present in M. cordata stems and root based on mass fragmentation of isoquinoline alkaloids. Currently, 10 benzyltetrahydroisoquinoline alkaloids have been identified from Macleaya , which are papaverine ( 13 ), laudanine ( 14 ), codamine ( 15 ), pseudocodamine ( 16 ), magnocurarine ( 17 ), reticuline ( 18 ), N ‐methylcoclaurine ( 19 ), 2‐methoxylmagnocurarine ( 20 ), colletine ( 21 ), and N‐ demethylcolletine ( 22 ) (Qing, ; Yu, Zuo, Qing, Yang, & Zeng, ; Zuo et al, ).…”
Section: Phytochemistrymentioning
confidence: 99%
“…Compounds 101–105 were speculated to be present in M. cordata based on mass fragmentation of isoquinoline alkaloids. Besides, Zuo et al () detected three tetrahydroprotoberberine alkaloids ( 106–108 ) first time in the fresh roots of M. cordata that were intermediate alkaloids in sanguinarine and chelerythrine biosynthetic pathways or speculated to be involved in the new branches.…”
Section: Phytochemistrymentioning
confidence: 99%
See 1 more Smart Citation